Pendekatan Inovatif Dalam Pengembangan Peserta Didik Berdasarkan Karakteristik - Wahyuni, Andi Eki Dwi; Damopolii, Muljono; Yuspiani, Yuspiani (LPPM Institut Pendidikan Nusantara Global, 2025)
Education aims to develop the potential of students holistically through cognitive, affective, and psychomotor aspects. Characteristic-based development of students allows learning to be designed according to their unique needs, including learning styles, multiple intelligences, and social and cultural backgrounds. This article examines the strategy of developing students based on characteristics using a descriptive-analytical literature review method. The results of the study indicate that strategies that focus on student characteristics, such as problem-based and project-based learning, are able to optimize the development of cognition, affectivity, and psychomotor in a balanced manner. This approach supports the creation of effective learning that not only builds knowledge, but also positive attitudes and practical skills, so that students develop into individuals with character and competitiveness.